Improvement of Open-Circuit Voltage in Organic Photovoltaic Cells with Chemically Modified Indium-Tin Oxide - Sarangerel, Khayankhyarva; Delgertsetseg, Byambasuren; Javkhlantugs, Namsrai; Sakomura, Masaru; Ganzorig, Chimed (Scientific research, 2013)
The possibility of the increase in open-circuit voltage of organic photovoltaic cells based primarily indium-tin oxide (ITO)/rubrene/fullerene/Al structure by changing the work function of ITO anodes and Al cathodes was described in this work. To change built-in potential preferably in order to increase the open-circuit voltage, the work function of ITO should be increased and work function of Al should be decreased. The correlation between the change in work functions of electrodes and performance of the organic photovoltaic cells before and after surface modifications was examined in detail. The enhancement of open-circuit voltage depends on a function of work function change of both ITO and Al electrode. We could show that the built-in potential in the cells played an important role in open-circuit voltage
Keywords: Open-Circuit Voltage; Chemical Modification; Indium-Tin Oxide